Menopausal hormone therapy and venous thromboembolism - Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2014)
Menopausal hormone therapy (MHT) is the most effective method of treating vasomotor symptoms and other climacteric symptoms related to estrogen deficiency in peri- and postmenopausal period. In addition to estrogen replacement, women with preserved uterus require the addition of progestagen in order to ensure endometrial safety. One of rare but severe complications of MHT is venous thromboembolism (VTE). The incidence of VTE rises in parallel to women’s age and body weight. The condition is also linked to hereditary and acquired risk factors. Oral estrogens increase the risk of venous thromboembolic complications to varying extents, probably depending on their type and dose used. Observational studies have not found an association between an increased risk of VTE and transdermal estrogen treatment regardless of women’s age and body mass index (BMI). Micronized progesterone and pregnanes, including dydrogesterone, have no effect on the risk of VTE, whereas norpregnane progestagens cause an additional increase in risk. Among hormonal preparations which are commercially available in Poland, the combination of transdermal estradiol with oral dydrogesterone appears to be the optimum choice, as it does not elevate the risk of VTE (compared to patients not using MHT), and dydrogesterone seems to be the progestagen of choice.